Structural and functional analyses of the fosfomycin resistance transposon Tn2921. - Navas, J (1985)
The fosfomycin resistance transposon Tn2921 is flanked by directly repeated sequences homologous to the Tn10-related insertion sequence IS10. The nonrepeated DNA sequences of Tn2921 can be deleted without affecting the transposition ability of the element, showing that at least one of the direct repeats is an active insertion sequence. Transposition of Tn2921 seems to occur through direct transposition, since cointegrates have not been observed. The evolutionary relatedness of Tn2921 and IS10 is discussed.